The 30 day MBA in business finance : your fast track guide to business success - Barrow, Colin, 1941- (Kogan Page, 2016)
"The 30 Day MBA in Business Finance draws on 13 fundamental disciplines that form the basis of a modern MBA finance course. This revised and updated second edition provides guidance on understanding financial reports, assessing the credit worthiness of business partners, determining profitable strategies, raising finance and ensuring proper records. Though based on UK accounting practice, the book makes readers more marketable as job candidates by offering them a wider view of finance. With new case studies, links to valuable online resources and self-assessment tests, this practical and accessible guide contains everything needed to eliminate gaps in financial knowledge, think like a financial strategist and become a top manager. "--Resumé vydavatele
Obsahuje webové odkazy a rejstřík
Keywords: MBA (Master of business administration degree); finance podniku; rozhodování; rizikový management; studium a výuka; business finance; decision making; risk management; study and teaching; učební texty; příručky; educational texts; handbooks and manuals